The Effect of Multi-Representation-Based Physics Learning on Students’ Representation Translation Ability in Linear Motion Topics - Amelia, Citra; Efendi, Ridwan; Sari, Ika Mustika (FKIP Universitas Lampung, 2025)
The students' disinterest and low ability to understand and translate physics concepts are challenges in physics learning. One of the solutions in this field is to implement a learning approach that can enhance students' interest and deepen their understanding and ability to translate abstract concepts of physics. This study aims to investigate the effect of implementing multi-representation-based physics learning on students’ representation translation abilities in linear motion. This study employs a quasi-experimental design with a non-equivalent control group pretest-posttest. This study involved 62 students from two eleventh-grade classes at senior high schools in Bandung, which were selected using purposive sampling. The experimental group received Lesh-Janvier multi-representation-based learning treatment, while the control group received conventional teacher-centered learning treatment. These research instruments include tests for representation translation ability and student response questionnaires. The results indicate that the representation translation ability of the experimental group shows a significant improvement, with an n-gain value of 0.74. Students’ responses to the learning process were also positive. Hypothesis testing using IBM SPSS shows a significant result (Asymp. Sig. < 0.001) for the experimental group, indicating a significant difference. Thus, multi-representation-based learning positively affects students' representation translation abilities. Keywords: multi representations, representation translation ability, linear motion.